Legal Review of Tackling Cases of Illegal Racing in Barru Regency, Indonesia - Mahmud, Mustakim; Risqilah, R. (Golden Ratio of Data in Summary, 2025)
This background explains the various methods employed by the people in the Barru District. The results of this research investigate several cases of illegal racing involving young people in the area. The study outlines various efforts by the police to curb illegal racing, which poses a threat to both public safety and the safety of the participants. To prevent such activities, the police conduct patrols, conduct inspections, regulate traffic, and organize official racing events as a legal alternative for motorcycle enthusiasts. This research also discusses the social issues in Barru Regency and highlights the role of the community in addressing these problems. The findings are expected to assist in developing public policies that more effectively address illegal racing and improve regional security.